Putusan Verstek Terhadap Perkara Cerai Gugat Suami Ghaib di Pengadilan Agama Surabaya: (Putusan Nomor 1301/Pdt.G/2024/PA.Sby) - Dewinda Ari Fitriyani; Indah Purbasari (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Marriage is a sacred relationship that occurs between a man and a woman with the aim of building a prosperous family. However, in reality, family life can face various situations that cause unhappiness and lead to the dissolution of a marriage. One example of divorce is when a husband disappears without a trace, leaving his wife behind. This research aims to explain and examine the supernatural divorce case based on decision number 1301/Pdt.G/2024/PA.Sby and analyze the judge's considerations in making decisions regarding the case. This research uses normative legal methods, with data collection techniques through literature review. The judge's reasons in cases of unseen divorce include the absence of the defendant whose whereabouts have not been identified or who have been declared missing, as well as the existence of documents from the sub-district explaining the ignorance of the position of the party concerned. The trial can be terminated in verstek if the defendant, having been legally summoned by the court, is still absent for no apparent reason..